Flight activity in relation to flight muscle and wing area in three insect species (Bangladesh Journal of Zoology, 2025)
Factors like larger wings, greater thorax mass, a higher thorax-abdomen ratio, more stored reserves, and lower wing loading enhance flight performance, movement and dispersal. This study assessed the flight activity of three species—Melanitis leda (both male and female), Apis dorsata (worker female), and Calliphora sp. (both male and female)—and evaluated their dorsolongitudinal flight muscle (DLM) and forewing area. Tethered technique was used to observe the flight activity. A. dorsata showed the longest mean flight duration (4.14 min), followed by male M. leda (2.30 min), female M. leda (1.42 min), female Calliphora sp. (1.35 min), and male Calliphora sp. (0.19 min). In M. leda, male flight activity correlated positively with forewing volume (r = 0.565) and negatively with DLM volume (r = -0.91), while female showed strong positive correlation with forewing volume (r = 0.925) and weak positive correlation with DLM volume (r = 0.274). In A. dorsata, flight activity slightly decreased with larger wings (r = -0.07) and DLM (r = -0.560). In Calliphora sp., male showed negative correlations with forewing (r = -0.328) and DLM volumes (r = -0.567), while female showed positive (r = 0.316) and weak negative (r = -0.089) correlations, respectively. These findings highlight the complex interplay between flight morphology and activity, offering new insights into the conservation strategies of different insect species.Bangladesh J. Zool. 53(1): 99-109, 2025